The Integration of National and Local Curricula: A Framework for Shaping the Muslim Personalities of Students at Madrasah Diniyah Takmiliyah Ula Al-Hidayah Klaten - Musthova, Arifin; Nur Khalim, Ahmad Dwi (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: This study explores the integration of national and local curricula at Madrasah Diniyah Takmiliyah Ula Al-Hidayah, a non-formal Islamic educational institution in Klaten, in shaping the Muslim character of students. Employing a qualitative case study approach, it examines the implementation of learning strategies rooted in religious values and local wisdom to develop students’ spirituality, morality, intellectuality, and professionalism. Data collection through triangulation—including interviews, observations, and document analysis—provides detailed insights into curriculum integration and its impact on shaping student character. The findings reveal that integrating national and local curricula has successfully enhanced students’ understanding of local religious and cultural values, as evidenced by their daily behavior. Nonetheless, challenges persist, particularly in ensuring the availability of supporting resources. The study's limitations include its focus on a single institution and a relatively short observation period, which restrict the generalizability of its findings. This research contributes to the discourse on Islamic education curriculum development by underscoring the significance of harmonizing religious values and local wisdom for holistic education. Future research could explore curriculum integration across diverse educational settings and develop more comprehensive evaluation models. The study highlights the need for innovative curriculum design to nurture a generation of Muslim students equipped to adapt to contemporary challenges.   Abstrak: Penelitian ini mengkaji integrasi kurikulum nasional dan lokal di Madrasah Diniyah Takmiliyah Ula Al-Hidayah, lembaga pendidikan Islam nonformal di Klaten, dalam membentuk kepribadian Muslim santri. Dengan menggunakan metodologi studi kasus kualitatif, penelitian ini berfokus pada implementasi strategi pembelajaran berbasis nilai agama dan kearifan lokal untuk mengembangkan kepribadian muslim pada aspek spiritualitas, moralitas, intelektualitas, dan profesionalitas santri. Triangulasi data, yang melibatkan wawancara, observasi, dan analisis dokumen, memberikan data mendalam tentang integrasi kurikulum dan dampaknya terhadap pembentukan kepribadian santri. Temuan utama menunjukkan bahwa integrasi kurikulum nasional dan lokal berhasil meningkatkan pemahaman nilai-nilai agama dan budaya lokal, sebagaimana tercermin dari perilaku santri dalam kehidupan sehari-hari. Namun, penelitian ini juga mengidentifikasi tantangan dalam pelaksanaan kurikulum, terutama dalam penyediaan sumber daya pendukung. Keterbatasan penelitian ini terletak pada lingkup yang terbatas pada satu institusi serta durasi observasi yang relatif singkat, yang membatasi generalisasi temuan. Penelitian ini berkontribusi pada diskusi tentang pengembangan kurikulum pendidikan Islam, menekankan pentingnya kolaborasi antara nilai religius dan kearifan lokal untuk pendidikan yang holistik. Arah penelitian masa depan mencakup eksplorasi implementasi integrasi kurikulum di berbagai lembaga pendidikan serta model evaluasi yang lebih komprehensif. Studi ini menekankan pentingnya inovasi desain pengembangan kurikulum untuk membangun generasi santri yang berkepribadian Muslim yang adaptif terhadap tantangan zaman.